2017
DOI: 10.1155/2017/7878605
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Immune Thrombocytopenia Outcome in Greek Children: A Retrospective Single-Centered Analysis

Abstract: Immune thrombocytopenia (ITP) in children has a varied course and according to duration is distinguished as newly diagnosed (<3 months), persistent (3–12), and chronic (>12) types. Several studies have evaluated the prognostic factors for the progression of the disease, but similar works have yet to be performed in Greece. We aimed to identify prognostic markers for the three forms of the disease in 57 Greek children during a 13-year period. Information regarding age, gender, preceding infection, bleeding type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 28 publications
2
13
1
Order By: Relevance
“…Jung et al reported that 85.9% of children with ITP would have remission and 14.1% would have chronic ITP; the prognostic factors for chronic ITP are children of an older age and the slow appearance of clinical symptoms [ 27 ]. Makis et al reported that the prognostic factors for developing chronic ITP are age >10 years, no previous infection history, longer duration of clinical manifestations, and initial platelet count >10 000/uL [ 28 ]. Other investigators reported that the prognostic factors that provided complete remission when ITP was established were a low mean platelet volume level <8 fL and previous infection history [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jung et al reported that 85.9% of children with ITP would have remission and 14.1% would have chronic ITP; the prognostic factors for chronic ITP are children of an older age and the slow appearance of clinical symptoms [ 27 ]. Makis et al reported that the prognostic factors for developing chronic ITP are age >10 years, no previous infection history, longer duration of clinical manifestations, and initial platelet count >10 000/uL [ 28 ]. Other investigators reported that the prognostic factors that provided complete remission when ITP was established were a low mean platelet volume level <8 fL and previous infection history [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, sex, age, and platelet counts were considered as important risk factors for chronic disease in our study. In another study, Makis et al examined the relationship of different risk factors with the development of chronic ITP in 57 children [12]. Multiple logistic regression models were used to investigate the association of age, sex, history of infection, type of bleeding, duration of symptoms, platelet count at diagnosis, treatment process, and immunological markers with chronic ITP.…”
Section: Discussionmentioning
confidence: 99%
“…Current treatment of ITPs includes the use of IVIG or steroids, anti-D, and in some cases only the patient is monitored [9]. Old age, female gender, and the onset of disease, silence have been suggested as risk factors for chronic disease [10], [11], [12], but unfortunately it is unclear, which what is the relationship between disease time and the number of bone marrow megakaryocytes. Given the absence of a standard for the chronic type ITP, identifying the risk factors involved in the onset and early diagnosis of the disease is very valuable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, 2 observational studies in children have referred to the association of platelets with ITP, but the results were inconsistent. One of the studies found that persistent ITP had a significantly lower initial platelet count compared with newly diagnosed ITP [29]; another study concluded that initial platelet count was not associated with GC resistance [30]. Therefore, in view of the aforementioned evidence, we used the ratio of the 2 to observe their association with GC resistance.…”
Section: Discussionmentioning
confidence: 99%